2014
DOI: 10.1055/s-0034-1373667
|View full text |Cite
|
Sign up to set email alerts
|

A Case of a Beta-Human Chorionic Gonadotropin Secreting Sinonasal Teratocarcinosarcoma

Abstract: Background and Importance Sinonasal teratocarcinosarcoma (SNTCS) is an unusual and aggressive neoplasm characterized by the combination of teratoma and carcinosarcoma features that is often misdiagnosed based on a biopsy sample. Approximately 60 cases have been reported in the English literature, but none have been associated with serum tumor markers. We report a case of SNTCS with elevation of serum β-human chorionic gonadotropin (hCG) level. Clinical Presentation The patient was a 22-year-old pregnant woman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“… 6 , 7 The incidence is relatively low, with fewer than 150 cases reported worldwide and only ∼10 cases in China. We reviewed the literature from 1968 to 2020, and 107 SNTCS cases were identified during this period ( Table 1 ) 5 , 8 – 22 .…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 The incidence is relatively low, with fewer than 150 cases reported worldwide and only ∼10 cases in China. We reviewed the literature from 1968 to 2020, and 107 SNTCS cases were identified during this period ( Table 1 ) 5 , 8 – 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature revealed 11 cases of TCS with intracranial invasion [ Table 1 ]. [ 3 6 7 8 9 16 17 19 20 21 ] Although the documented cases with predominant intracranial involvement are scarce, treatment with surgical resection with or without adjuvant treatments of chemotherapy and radiation therapy is the most widely accepted with goal for gross total resection. Despite few intracranial cases described in the literature, patients undergoing gross total resection fare better than those with subtotal resection.…”
Section: Discussionmentioning
confidence: 99%